Thymus, undernutrition, and infection: Approaching cellular and molecular interactions - Savino, Wilson; Durães, Jonathan; Maldonado-Galdeano, Carolina; Perdigon, Gabriela; Mendes-da-Cruz, Daniella Arêas; Cuervo, Patricia (Frontiers in Nutrition, 2022)
Undernutrition remains a major issue in global health. Low protein-energy consumption, results in stunting, wasting and/or underweight, three deleterious forms of malnutrition that affect roughly 200 million children under the age of five years. Undernutrition compromises the immune system with the generation of various degrees of immunodeficiency, which in turn, renders undernourished individuals more sensitive to acute infections. The severity of various infectious diseases including visceral leishmaniasis (VL), influenza, and tuberculosis is associated with undernutrition. Immunosuppression resulting from protein-energy undernutrition severely impacts primary and secondary lymphoid organs involved in the response to related pathogens. The thymus - a primary lymphoid organ responsible for the generation of T lymphocytes - is particularly compromised by both undernutrition and infectious diseases. In this respect, we will discuss herein various intrathymic cellular and molecular interactions seen in undernutrition alone or in combination with acute infections. Many examples illustrated in studies on humans and experimental animals clearly revealed that protein-related undernutrition causes thymic atrophy, with cortical thymocyte depletion. Moreover, the non-lymphoid microenvironmental compartment of the organ undergoes important changes in thymic epithelial cells, including their secretory products such as hormones and extracellular matrix proteins. Of note, deficiencies in vitamins and trace elements also induce thymic atrophy. Interestingly, among the molecular interactions involved in the control of undernutrition-induced thymic atrophy is a hormonal imbalance with a rise in glucocorticoids and a decrease in leptin serum levels. Undernutrition also yields a negative impact of acute infections upon the thymus, frequently with the intrathymic detection of pathogens or their antigens. For instance, undernourished mice infected with Leishmania infantum (that causes VL) undergo drastic thymic atrophy, with significant reduction in thymocyte numbers, and decreased levels of intrathymic chemokines and cytokines, indicating that both lymphoid and microenvironmental compartments of the organ are affected. Lastly, recent data revealed that some probiotic bacteria or probiotic fermented milks improve the thymus status in a model of malnutrition, thus raising a new field for investigation, namely the thymus-gut connection, indicating that probiotics can be envisioned as a further adjuvant therapy in the control of thymic changes in undernutrition accompanied or not by infection.